Firm Innovativeness and Its Performance Outcomes: A Meta-Analytic Review and Theoretical Integration - Rubera, Gaia; Kirca, Ahmet H. (Journal of Marketing, 2012)
Drawing on the chain-of-effects model as a unifying framework, this meta-analysis indicates that firm innovativeness indirectly affects firm value through its effects on market position and financial position. In addition, the findings suggest that innovativeness has direct positive effects on financial position and firm value. Moreover, the meta-analysis provides evidence of reverse causality in the innovativeness–firm value relationship. Importantly, the results also reveal that the positive effects of firm innovativeness on market position and financial position are stronger for larger firms, for firms that invest more in advertising, for firms in high-tech industries, for innovativeness outputs and for radical innovations. Finally, the meta-analytic evidence also indicates that the relationship between innovativeness and firm value is stronger for smaller firms, for firms that invest more in advertising, for firms in low-tech industries, for innovativeness inputs, for innovativeness culture, and for radical innovations.